(3GdebUO GdLdjd aj cga LHQjds - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s; (3YRjR Hf TOGOs
(3ChdgG (B:s
(3GdMeO ddg GdPi bQH Edi LfGHg ef GNJGQg s
(3ahJhZQa Yf NW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B260 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3eLGejY (B372) s
Keywords: (3GdJGQjNs